2021
DOI: 10.1021/acsami.0c20500
|View full text |Cite
|
Sign up to set email alerts
|

Activation Strategy of MoS2 as HER Electrocatalyst through Doping-Induced Lattice Strain, Band Gap Engineering, and Active Crystal Plane Design

Abstract: Doping engineering emerges as a contemporary technique to investigate the catalytic performance of MoS 2 . Cation and anion co-doping appears as an advanced route toward electrocatalytic hydrogen evolution reaction (HER). V and N as dopants in MoS 2 (VNMS) build up a strain inside the crystal structure and narrow down the optical band gaps manifesting the shifting of the absorbance band toward lower energy and improved catalytic performance. FE-SEM, HR-TEM, and XRD analysis confirmed that V and N doping decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
75
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(79 citation statements)
references
References 68 publications
4
75
0
Order By: Relevance
“…[18][19][20] A lot of reported theoretical and experimental research in the related fields has indicated that the most active sites in 2H-MoS 2 are located at the edges, while the poor electrical conductivity of MoS 2 basal planes is generally bad for catalysis of the HER. 15,21,22 Therefore, in order to solve the above obstacles, many modified methods have been conducted to enhance the catalytic capacity of MoS 2 in HER, involving doping, 23,24 building up of hybrid structures, 2,25,26 crystalline phase and band-gap engineering 27,28 and so on. Compared with doping or phase transition engineering, the process of constructing composite nanostructure heterojunctions is simple and cost-effective.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] A lot of reported theoretical and experimental research in the related fields has indicated that the most active sites in 2H-MoS 2 are located at the edges, while the poor electrical conductivity of MoS 2 basal planes is generally bad for catalysis of the HER. 15,21,22 Therefore, in order to solve the above obstacles, many modified methods have been conducted to enhance the catalytic capacity of MoS 2 in HER, involving doping, 23,24 building up of hybrid structures, 2,25,26 crystalline phase and band-gap engineering 27,28 and so on. Compared with doping or phase transition engineering, the process of constructing composite nanostructure heterojunctions is simple and cost-effective.…”
Section: Introductionmentioning
confidence: 99%
“…[ 17–19 ] The class of layered transition metal dichalcogenides (TMDs) has represented a workhorse in the research field of EC for the hydrogen evolution reaction (HER), as testified by the wide literature available. [ 20–25 ] Experimental studies have been coupled with theoretical calculations to identify the location of the catalytic sites (e.g., defective edges [ 26–28 ] and basal planes [ 29–31 ] ), while clarifying the activity of their different phases (e.g., 1T, [ 32,33 ] 1T’, [ 34–36 ] 2H, [ 34 ] 3R [ 37,38 ] and 6R [ 39 ] ), as well as the effects of strain engineering [ 40–43 ] and chemical doping. [ 40,41,44,45 ]…”
Section: Introductionmentioning
confidence: 99%
“…Figure 27 LSV curves of (a) Pd3P2S8, (b) N-5h-Pd3P2S8, (c) N-10h-Pd3P2S8, and (d) Pt/C catalysts in O2-saturated 0.1 M KOH solution at different rotation speeds with a sweep rate of 10 mV s -1 . Inset: Koutecky-Levich plots (i −1 vs. ω −1/2 ) relationship.…”
Section: Figure 25mentioning
confidence: 99%
“…In fact, MoS2 and WS2 had been widely researched for their use as electrocatalyst as well because of the ability to tune sulfur vacancies through defects engineering. 26,27 Precious metal TMDs such as that based on platinum (Pt) and palladium (Pd) are well known for their electrical properties and electrochemical capability, 28 yet, there is a need to activate the material to increase the mass activity and to boost the efficiency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation